The Impact of Service Quality and Facilities on Customer Satisfaction at Cinta Jawa Cafe Restaurant, Tokyo - Cindy Cornelia; Dewi Kusumaningrum (Politeknik Sahid, 2026)
This study examines how service quality and facilities influence customer satisfaction at Cinta Jawa Cafe in Tokyo. A quantitative survey was administered to 75 customers and analyzed using multiple linear regression, supported by t-tests for partial effects and an F-test for the overall model. The respondent profile was dominated by men (53%), aged 17–27 (68%), with senior high school education (45%), and mostly students (46%); nearly half reported monthly food-and-beverage spending of 10,000–30,000 yen (49%), suggesting a young, value-oriented market segment. The results indicate that service quality has a positive and statistically significant effect on customer satisfaction (Sig = 0.000; t = 4.826), implying that timely, accurate, and courteous service plays a decisive role in shaping satisfaction. In contrast, facilities show no significant partial effect in the combined model (Sig = 0.651; t = 0.454), which may reflect overlapping variance with service-quality perceptions or a stronger customer emphasis on the service process than on physical attributes. Despite this, the model is significant simultaneously (Sig = 0.000; F = 32.308), confirming that the predictors jointly explain meaningful variation in satisfaction. The study contributes by providing evidence from an Indonesian restaurant context in Tokyo, where empirical findings on the relative importance of service quality versus facilities remain limited, and offers practical insight that managerial priorities should center on strengthening service performance while maintaining adequate physical conditions.